2018
DOI: 10.4172/2157-7145.1000406
|View full text |Cite
|
Sign up to set email alerts
|

Study of consanguinity of the population of northern Morocco

Abstract: Consanguinity is a matrimonial behavior that is much perpetuated in the Arabo-Muslim world. This behavior contributes to the impoverishment of the genetic heritage of populations by increasing the genetic homogeneity, influencing, thus, the state of the public health. Belonging to the Arabo-Muslim world, the North population of Morocco has been partially studied to characterize this matrimonial behavior from an anthropogenetic point of view.Sample of 1588 couples belonging to the population of northern Morocco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Previous works showed that the national consanguinity rate in Morocco varied between 19.81 and 28% [6]. Northern regions registered the highest rates with 39.4% (FI = 0.02033) in the Tangier-Tetouan region [6] and 24.37% (FI = 0.008038) in the Tangier-Tetouan-Al Hoceima region [4]. The Gharb-Chrarda-Beni Hssen region, the neighbor region, also registered a high rate of consanguinity (22.8%) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works showed that the national consanguinity rate in Morocco varied between 19.81 and 28% [6]. Northern regions registered the highest rates with 39.4% (FI = 0.02033) in the Tangier-Tetouan region [6] and 24.37% (FI = 0.008038) in the Tangier-Tetouan-Al Hoceima region [4]. The Gharb-Chrarda-Beni Hssen region, the neighbor region, also registered a high rate of consanguinity (22.8%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven percent of the global population is married to a kinsperson [3]. The Middle East and North Africa are known for high levels of consanguineous kinships compared to Western countries [4]. In Morocco, consanguinity varies in the range of 19.81–28% [5].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with the previous study which showed that the consanguinity rate in Eastern Morocco region is higher than the national average (29.58% vs. 22.79%) (Mohammed et al, 2019;Talbi et al, 2007). Thereby, it is not surprising to see a strong occurrence of autosomal recessive diseases such as thalassemia in our population (Habibeddine et al, 2018;Jaouad et al, 2009;Laghmich et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…However, unlike ALS, its systemic involvement is far-reaching and responsible for a clinical picture including several neurological findings, such as motor and sensory neuropathies, cerebellar impairment, visual and auditory issues, as well as musculoskeletal deformities, cardiovascular problems and diabetes [ 4 ]. The condition is an autosomal recessive disorder and, given the high rate of consanguinity in several areas in the country, we suspect there might be a higher prevalence of the condition in Morocco than elsewhere [ 37 ]. Out of the 5 cases identified in our patients, 2 were a brother and a sister from a consanguineous marriage.…”
Section: Discussionmentioning
confidence: 99%